Ritual of Maudu Lompoa in South Sulawesi Indonesia: An Islamic Economy Perspective - Rahim, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
It is a descriptive study of the Maudu Lompoa Ritual that conducted in Cikoang Takalar village of South Sulawesi, Indonesia. The purpose of this study was to find (1) the implementation of the Maudu Lompoa Ritual, and (2) how the Islamic Economy views the ritual. The results of this study are as follows. First, the ritual is conducted to celebrate the birthday of Prophet Muhammad as the greatest prophet in Islam. It is celebrated luxuriously. The phase of the ritual consists of A'jene-jene sappara (taking a bath), Anynyongko jangang (confining chicken), Angngalloi ase (drying rice), A'dengka ase (pounding rice), and A'tanak minynyak (making oil from coconut), and finally, celebrating it. However, it is found that the ritual tends to waste money. It is not suitable for the Islamic economy perspective. Therefore, it is suggested that the ritual should be examined, whether it is appropriate to be conducted in Indonesia or not.